2011
DOI: 10.2903/j.efsa.2011.2171
|View full text |Cite
|
Sign up to set email alerts
|

Scientific Opinion on the safety and efficacy of vitamin B6 (pyridoxine hydrochloride) as a feed additive for all animal species

Abstract: Pyridoxine hydrochloride is a form of vitamin B 6 , an essential micronutrient. Oral administration routes of pyridoxine hydrochloride via feed or water are considered as bioequivalent. Pyridoxine hydrochloride is considered to be safe for all animal species at the commercial use levels. The FEEDAP Panel concludes that the use of pyridoxine hydrochloride as a nutritional additive does not give rise to concern for consumers. Pyridoxine hydrochloride is not an irritant to skin and eyes; it is not a skin sensitiz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 20 publications
1
7
0
Order By: Relevance
“…In the previous assessments of the FEEDAP Panel, the overall vitamin B 6 intake was estimated to range between 1.2 and 2.8 mg/day, with food of animal origin contributing to about 50% of the total intake from food sources. The FEEDAP Panel concluded that there was no risk to exceed the UL of 25 mg/day from food sources and that the use of vitamin B 6 as nutritional additive in feed for food producing animals is safe for the consumer (EFSA FEEDAP Panel, 2010, 2011.…”
Section: Reassessment Of Consumer Exposurementioning
confidence: 99%
See 1 more Smart Citation
“…In the previous assessments of the FEEDAP Panel, the overall vitamin B 6 intake was estimated to range between 1.2 and 2.8 mg/day, with food of animal origin contributing to about 50% of the total intake from food sources. The FEEDAP Panel concluded that there was no risk to exceed the UL of 25 mg/day from food sources and that the use of vitamin B 6 as nutritional additive in feed for food producing animals is safe for the consumer (EFSA FEEDAP Panel, 2010, 2011.…”
Section: Reassessment Of Consumer Exposurementioning
confidence: 99%
“…The safety of pyridoxine hydrochloride for the target species, consumers, users and the environment has been evaluated in previous opinions (EFSA FEEDAP Panel, 2010, 2011. The FEEDAP Panel concluded that pyridoxine hydrochloride is considered to be safe for all animal species at the commercial use levels and that the use of pyridoxine hydrochloride as a nutritional additive does not raise safety concerns for consumers and the environment.…”
Section: Safetymentioning
confidence: 99%
“…The EFSA Scientific Panel on Additives and Products or Substances used in Animal Feed (FEEDAP) issued two opinions on the safety and efficacy of vitamin B 6 , in the form of pyridoxine hydrochloride, when used as a feed additive for all animal species (EFSA FEEDAP Panel, 2010, 2011.…”
Section: Additional Informationmentioning
confidence: 99%
“…The safety of pyridoxine hydrochloride for the target species, consumers, users and the environment was evaluated in previous opinions (EFSA FEEDAP Panel, 2010, 2011. The FEEDAP Panel concluded that pyridoxine hydrochloride is considered to be safe for all animal species at the commercial use levels and that the use of pyridoxine hydrochloride as a nutritional additive does not give rise to concern for consumers and the environment.…”
Section: Safetymentioning
confidence: 99%
See 1 more Smart Citation